ENLIGHTENMENT AND LITERARY CRITICISM - Mizrabova Jeren Ismailovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article provides a comprehensive overview of the development of European literary criticism from the Renaissance to the Enlightenment and Neoclassicism. The study focuses on key figures and theoretical models that shaped the evolution of critical thought, ranging from P. Sidney and his defense of poetry as a morally significant art form to J. Dryden, A. Pope, and S. Johnson, who established the foundations of Neoclassical aesthetics and criticism. The analysis addresses the main aesthetic principles of the classical tradition, including mimesis, catharsis, the three unities, and the concept of “art as imitation.”